2020
DOI: 10.1101/2020.03.18.20038067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-Sex based estimates of risk of death from COVID Infection in Adult Cancer Patients

Abstract: The SARS-CoV-2 (COVID-19) novel corona virus represents a significant health risk, particularly in older patients. Cancer is one of the leading causes of death in most rich countries, and delivering chemotherapy may be associated with increased risk in the presence of a pandemic infection. Estimating this risk is crucial in making decisions about balancing risks and benefits from administering chemotherapy. However, there are no specific data about chemotherapy risks per se. Here we develop a simple model to e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Further there are concerns regarding chemotherapy administration in the elderly with cancer. In a modeling study, it was estimated that the case fatality rate from COVID-19 infection in a 70-year-old patient may be 2- to 3-folds higher than the 5% survival benefit from chemotherapy [24] . Thus, in the context of pandemic-related limitations on access, the initial treatment should be that which provides the highest cure fraction, e.g., radical cystectomy.…”
Section: Delayed Surgery and Adverse Outcomesmentioning
confidence: 99%
“…Further there are concerns regarding chemotherapy administration in the elderly with cancer. In a modeling study, it was estimated that the case fatality rate from COVID-19 infection in a 70-year-old patient may be 2- to 3-folds higher than the 5% survival benefit from chemotherapy [24] . Thus, in the context of pandemic-related limitations on access, the initial treatment should be that which provides the highest cure fraction, e.g., radical cystectomy.…”
Section: Delayed Surgery and Adverse Outcomesmentioning
confidence: 99%
“…As the coronavirus disease (COVID-19) pandemic unfolds, there is emerging evidence that patients with cancer are particularly vulnerable to infection and adverse events, with poorer outcomes than the general population (1,2). In response, cancer centers and physicians around the world are rapidly trying to determine the best strategies to protect patients with cancer from COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In carcinoma ovary, a retrospective study by Starbuck et al [14] has shown that timely chemotherapy completion was associated with better survival and high complete response rates. It was seen by Williams et al that mortality from chemotherapy was doubled in the presence of COVID-19 infection, in the age group of over 50 years [15]. In patients who were initiated on neoadjuvant chemotherapy, plans were modified to complete chemotherapy to six cycles instead of the usual three before assessment for interval debulking surgery.…”
Section: Discussionmentioning
confidence: 99%